2014
DOI: 10.5761/atcs.cr.12.02117
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stent-Graft for a Giant Bronchial Artery Aneurysm with Ultrashort Neck

Abstract: Bronchial artery aneurysms are rarely encountered, but they can cause life-threatening hemorrhages when they rupture. The authors report a case of a giant bronchial artery aneurysm with ultrashort neck in a 73-year-old woman who presented with massive hemoptysis. The aneurysm was successfully treated by a combination of transcatheter arterial embolization and aortic stent-graft placement, and the patient made an uneventful recovery. Follow-up computed tomography (CT) obtained 24 months after aortic stent-graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Thoracic aortic endovascular repair was selected to solve the short neck issue, as reported in 9 articles. [4,1219] In our case, we chose to implant a stent across the ectopic bronchial artery to avoid movement of the interlocking coils. To our best knowledge, this is the first time that combined TAE and stent was used in treating BAA.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic aortic endovascular repair was selected to solve the short neck issue, as reported in 9 articles. [4,1219] In our case, we chose to implant a stent across the ectopic bronchial artery to avoid movement of the interlocking coils. To our best knowledge, this is the first time that combined TAE and stent was used in treating BAA.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to achieve complete embolization in cases where the vascular segment between the aneurysm and aorta is short. 4 ) Revascularization of BAA is also reported by collateral vessels, incomplete embolization, and arterial re-canalization. 1 , 4 ) In addition, in cases where the neck of BAA is branched from the anterior surface of the descending aorta, the possibility of distal embolization is significant.…”
Section: Discussionmentioning
confidence: 98%
“…Since the retrograde blood flow to the aneurysm from the outflow vessel may remain, some authors recommended that TAE should be considered with the stent graft simultaneously. 1 , 2 , 4 ) Although the follow-up period was short, Kasashima et al 6 ) and Arici et al 10 ) reported acceptable results using stent graft treatment alone. We also examined TAE in our case; it seemed too technically demanding because there are multiple, thin, and tortuous inflow arteries.…”
Section: Discussionmentioning
confidence: 99%
“…TAE is often the first choice for a ruptured BAA because of its low invasiveness, although it is sometimes difficult when the aneurysm has a short neck. In such cases, previous studies reported the successful treatment effects of a stent graft for BAA (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) (Table). However, most of the treatments in these previous studies were indicated for an unruptured BAA, while only two reports indicated a ruptured BAA (8,15).…”
Section: Discussionmentioning
confidence: 99%